Remarkably Ruby - Libenson, Terri (New York, NY : Balzer + Bray, an imprint of HarperCollinsPublishers, 2022)
Although Ruby and Mia used to be friends, they've grown apart as Ruby is not a joiner and likes to write poetry, while Mia is popular and wants to be class president, but they may have more in common than they realize.
3-6
English.
Keywords: Friendship -- Juvenile fiction; Girls -- Juvenile fiction; Identity (Psychology) -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Friendship -- Fiction; Girls -- Fiction; Identity -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Friendship -- Fiction; Girls -- Fiction; Identity (Psychology) -- Fiction; Middle schools -- Fiction; School stories; Illustrated works; School fiction